The Implementation Of Make A-Match Model In Social Science Learning To Improve Student Learning Outcomes In Class IV SDN 115 Manado - Lompoliuw, B A (Journal of Educational Method and Technology, 2019)
There is a tendency in the education field today to return to the idea that children will learn better if the environment is created naturally. Learning will be more meaningful if children "experience" themselves what they are learning, not 'knowing' it. Target-oriented learning of material mastery proves to be successful in short-term 'remembering' competitions, but fails to equip children to solve problems in long-term life. The problems that would to be studied in this study are: (a) how is the improvement of Social Science learning outcomes by applying the Make A-Match Model to it? (b) how does the Make A-Match Model apply towards the learning motivation? The objectives of this study are: (a) want to know the improvement in Social Science learning achievement after the implemetation of the Make A-Match Model. (b) want to know the effect of Make A-Match Model towards studentsâ€™ motivation of the subject after it is applied. This research is used two rounds of action research. In each round consists of four stages, namely: design, activity and observation, reflection and revision. The target of this research is the fourth grade students of Mongodow. The data obtained in the form of formative test results, observation sheets of teaching and learning activities. From the results of analysts obtained student achievement has increased from cycle I to cycle II namely, cycle I (65%), cycle II (83%). The conclusion of this research is the Make A-Match Model of Social Science learning could positively influence the motivation of learning of central students, and this learning model could be used as an alternative to Social Science learning.Â Keywords: Make A-Match Model; Social Science Learning; Learning Outcome.